2021
DOI: 10.3390/jtaer16040056
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Adoption of Incentivized Word-of-Mouth in the Online Environment

Abstract: Nowadays, word-of-mouth is a very important component of e-commerce activity because consumers are very sensitive to other people’s opinions. Depending on the companies’ politics, these opinions can be incentivized or non-incentivized. One of the major dilemmas consists in establishing which kind of word-of-mouth has more influence on customers’ perceptions. The purpose of this study is to assess the relationships between perceived argument quality (PAQ) and perceived source expertise (PSE), on the one hand, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…These quazi-spontaneous posts, by private individuals, are seen as more objective, and therefore are more likely to be adopted by readers (i.e., Tsao and Hsieh [7] showed this to be the case, with an empirical examination of eWOM platforms). Likewise, Anastasiei, et al [8] modeled the factors which cause a consumer to "adopt" information contained with an eWOM (i.e., the factors which lead a consumer to incorporate that information into their purchase decision) and found that source credibility is central to information adoption. They further showed that source credibility is determined by perceived source (i.e., reviewer) expertise and perceived argument quality.…”
Section: Introductionmentioning
confidence: 99%
“…These quazi-spontaneous posts, by private individuals, are seen as more objective, and therefore are more likely to be adopted by readers (i.e., Tsao and Hsieh [7] showed this to be the case, with an empirical examination of eWOM platforms). Likewise, Anastasiei, et al [8] modeled the factors which cause a consumer to "adopt" information contained with an eWOM (i.e., the factors which lead a consumer to incorporate that information into their purchase decision) and found that source credibility is central to information adoption. They further showed that source credibility is determined by perceived source (i.e., reviewer) expertise and perceived argument quality.…”
Section: Introductionmentioning
confidence: 99%
“…Proof of Lemma 1. We give the detailed analysis process to obtain the equilibrium solutions for the model of a dominant platform whose decision problem can be determined by (5). To simplify analysis and without loss of generality, we consider two scenarios when T is larger or smaller, that is, T ≤ T 0 or T > T 1 .…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This is because fulfilling e-commerce orders depends on fast logistics, safe transportation (e.g., avoiding the spoilage of goods), and low transport costs [3]. Poor logistics, having an adverse effect on the reputation of e-commerce retailers [4], result in low sales and profits [5]. Through the rapid development of the past two decades, e-commerce has become the most commonly used way of purchasing.…”
Section: Introductionmentioning
confidence: 99%
“…Social media applications stimulate social interactions and user-generated content [28,29]. As they socialize online consumers generate eWOM by sharing recommendations and brand experiences with others [30].…”
Section: Literature Review and Theoretical Framework 21 Engagement With Ewom On Social Mediamentioning
confidence: 99%